The (cost-)effectiveness of an individually tailored long-term worksite health promotion programme on physical activity and nutrition: design of a pragmatic cluster randomised controlled trial - Burdorf Alex; Bredt Folef J; Robroek Suzan JW (BMC, 2007)
Abstract Background Cardiovascular disease is the leading cause of disability and mortality in most Western countries. The prevalence of several risk factors, most notably low physical activity and poor nutrition, is very high. Therefore, lifestyle behaviour changes are of great importance. The worksite offers an efficient structure to reach large groups and to make use of a natural social network. This study investigates a worksite health promotion programme with individually tailored advice in physical activity and nutrition and individual counselling to increase compliance with lifestyle recommendations and sustainability of a healthy lifestyle. Methods/Design The study is a pragmatic cluster randomised controlled trial with the worksite as the unit of randomisation. All workers will receive a standard worksite health promotion program. Additionally, the intervention group will receive access to an individual Health Portal consisting of four critical features: a computer-tailored advice, a monitoring function, a personal coach, and opportunities to contact professionals at request. Participants are employees working for companies in the Netherlands, being literate enough to read and understand simple Internet-based messages in the Dutch language. A questionnaire to assess primary outcomes (compliance with national recommendations on physical activity and on fruit and vegetable intake) will take place at baseline and after 12 and 24 months. This questionnaire also assesses secondary outcomes including fat intake, self-efficacy and self-perceived barriers on physical activity and fruit and vegetable intake. Other secondary outcomes, including a cardiovascular risk profile and physical fitness, will be measured at baseline and after 24 months. Apart from the effect evaluation, a process evaluation will be carried out to gain insight into participation and adherence to the worksite health promotion programme. A cost-effectiveness analysis and sensitivity analysis will be carried out as well. Discussion The unique combination of features makes the individually tailored worksite health promotion programme a promising tool for health promotion. It is hypothesized that the Health Portal's features will counteract loss to follow-up, and will increase compliance with the lifestyle recommendations and sustainability of a healthy lifestyle. Trial registration Current Controlled Trials ISRCTN52854353.